2016
DOI: 10.15694/mep.2016.000059
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between subjective well-being and empathy among Turkish medical students

Abstract: Background: Empathy as a part of humanistic medicine is an important component of medical education and could be taught throughout the years of medical study. In Turkey the national core medical curriculum is somewhat insufficient in terms of teaching empathy. In this study we wanted to measure empathy and to determine if there is a relationship between subjective well-being and empathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
3
1
3
Order By: Relevance
“…Results from studies on the effect of parents' education level on empathy in medical students are inconsistent. While some studies have found no significant relationship [30,31], one study revealed that the mother's education status affected medical students' levels of empathy [32]. Conversely, we found the father's education status to be associated with levels of empathy; students whose fathers' education was high school or below were higher in empathy than those students whose fathers had attained a more advanced education.…”
Section: Discussioncontrasting
confidence: 83%
“…Results from studies on the effect of parents' education level on empathy in medical students are inconsistent. While some studies have found no significant relationship [30,31], one study revealed that the mother's education status affected medical students' levels of empathy [32]. Conversely, we found the father's education status to be associated with levels of empathy; students whose fathers' education was high school or below were higher in empathy than those students whose fathers had attained a more advanced education.…”
Section: Discussioncontrasting
confidence: 83%
“…Fantasy reflects a tendency to identify with characters in fictional situations (movies, books) and help others; therefore, it may be associated with emotionality (Davis, 1980;Davis, 1983). Previous studies have shown a positive association between empathy and happiness among students; scores on perspective-taking and compassionate care were significantly positively related to happiness scores (Ozcakir et al, 2016). Empathy is also related to good communication skills and optimism (Hojat et al, 2015).…”
Section: Empathy and Life Satisfactionmentioning
confidence: 99%
“…Para conocer los niveles de empatía se aplicó la Escala de Empatía Médica de Jefferson (EEMJ) para profesiones de la salud versión estudiantes, validada en México y adaptada a Colombia a través del criterio de jueces, aunque su aplicación inicialmente fue en estudiantes de medicina, después se desarrolló una nueva versión ampliada a las diferentes profesiones de la salud la cual tiene leves modificaciones desde la versión original 34,35,[40][41][42][43][44] . La EEMJ para las profesiones de la salud versión estudiantes consta de 20 ítems tipo Likert en una escala de 1 a 7, donde 1 es totalmente en desacuerdo y 7 es totalmente de acuerdo; pero para evitar respuestas automáticas, la mitad de los ítems son negativos y por consiguiente la respuesta es invertida.…”
Section: Medición De Los Niveles De Empatíaunclassified
“…Para los análisis estadísticos la EMMJ se dividió en los tres factores, donde toma de perspectiva tiene puntajes entre 10 y 70 y comprende los ítems 2,4,5,9,10,13,15,16,17 y 20; cuidado con compasión tiene puntajes entre 8 y 56 y comprende los ítems 1,7,8,11,12,14,18 y 19; y ponerse en el lugar del paciente tiene puntajes entre 2 y 14 y comprende los ítems 3 y 6 44 . Con los datos suministrados se hicieron los análisis estadísticos correspondientes para el tipo de información, sin embargo, como limitante se reconoce que al tratarse de una muestra no aleatoria sus resultados no pueden ser extrapolados 45 .…”
Section: Medición De Los Niveles De Empatíaunclassified